Higher Education and International Student Mobility in the Global Knowledge Economy - Fletcher, Darla (Journal of International Students, 2012)
In the context of internationalization and globalization of higher education, Kemal Gürüz’s book, Higher Education and International Student Mobility in the Global Knowledge Economy, explores contributions made by international students and scholars in higher education from a historical perspective. A native of Turkey, Gürüz studied and worked for a while at Harvard University and the State University of New York in the United States. He presents the international mobility of students and scholars with in-depth historical, cultural and socio-economical perspectives. Gürüz highlights global knowledge economy, institutional patterns of higher education, enrollments, governance, and recent changes in higher education of several countries in this book.